2019
DOI: 10.1038/s41598-019-52567-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus velezensis 5113 Induced Metabolic and Molecular Reprogramming during Abiotic Stress Tolerance in Wheat

Abstract: Abiotic stresses are main limiting factors for agricultural production around the world. Plant growth promoting rhizobacteria (PGPR) have been shown to improve abiotic stress tolerance in several plants. However, the molecular and physiological changes connected with PGPR priming of stress management are poorly understood. The present investigation aimed to explore major metabolic and molecular changes connected with the ability of Bacillus velezensis 5113 to mediate abiotic stress tolerance in wheat. Seedling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 65 publications
1
39
0
17
Order By: Relevance
“…Treatment of wheat seedlings with Bacillus velezensis 5113 exposed to cold/freezing, heat or drought stress, improved the plant survival under stress conditions. Protein profile of wheat leaves showed differential expression of several proteins with cold stress showing strong impact on protein profile than heat and drought (Abd El-Daim et al, 2019). PGPR also help the plant under stress conditions by nutrient cycling through diazotrophy, phosphorus solubilization, and siderophore synthesis, by enhancing photosynthesis, increasing fine root production and overall root surface area and reducing the stress ethylene emission, thus contributing toward better plant performance (Casanovas et al, 2002;Timmusk et al, 2014;Gagné-Bourque et al, 2016).…”
Section: Pgpr and Abiotic Stress Tolerance In Plantsmentioning
confidence: 99%
“…Treatment of wheat seedlings with Bacillus velezensis 5113 exposed to cold/freezing, heat or drought stress, improved the plant survival under stress conditions. Protein profile of wheat leaves showed differential expression of several proteins with cold stress showing strong impact on protein profile than heat and drought (Abd El-Daim et al, 2019). PGPR also help the plant under stress conditions by nutrient cycling through diazotrophy, phosphorus solubilization, and siderophore synthesis, by enhancing photosynthesis, increasing fine root production and overall root surface area and reducing the stress ethylene emission, thus contributing toward better plant performance (Casanovas et al, 2002;Timmusk et al, 2014;Gagné-Bourque et al, 2016).…”
Section: Pgpr and Abiotic Stress Tolerance In Plantsmentioning
confidence: 99%
“…The rhizosphere chemistry and the development of plant-rhizomicrobiome interactions are still poorly characterised, however, emerging studies have reported that various PGPR species can pre-condition the plants for augmented defence responses against abiotic stresses [ 160 , 161 , 162 , 163 , 164 ]. The molecular mechanisms underlying the rhizobacteria-related defence priming show that this induced state suggests a reprogramming in the cellular metabolism and regulatory machinery of the plants.…”
Section: Microbial Biostimulants and Enhancement Of Plant Responses To Abiotic Stressesmentioning
confidence: 99%
“…Implementing a sustainable strategy to improve plant resistance against such environmental limitations is of great importance to secure and optimize global food production. One of the eco-friendly approaches is the application of PGPR and/or their byproducts (Mayak et al, 2004;Bano and Fatima, 2009;Piccoli and Bottini, 2013;Zafar-Ul-Hye et al, 2014;Qin et al, 2016;Abd El-Daim et al, 2019;Ipek et al, 2019), which can sustainably assist the plants to withstand the extreme environmental conditions (Table 1).…”
Section: Pgpr Derived Crop Tolerance Against Abiotic Stressesmentioning
confidence: 99%